Factors That Cause Families To Commit Crimes Against Children - Zhakilla Salsabilla Rizky Imani Pulubuhu; Lisnawaty Wadju Badu; Mellisa Towadi (Estudiante Law Journal, 2023)
This research aims to find out what factors cause families to commit criminal acts against children. This research uses empirical research methods by taking a qualitative approach. The results of this research found that cases of criminal acts against children occurred twice at the Gorontalo City Police in the past 3 years. In the child kidnapping case handled by the Gorontalo City Police, this case has become a case that has shocked Gorontalo residents recently. There was talk of a six year old child with the initials NV who suddenly disappeared and had even been searched for but not found around the city of Gorontalo until it was recently discovered that he had been taken by his aunt to Jakarta without his parents knowing. The perpetrator has been arrested by the Gorontalo City Police and stated that this case is currently in the second stage, namely the prosecutor's handling stage. Meanwhile, in the case of abuse that resulted in death, a five year old child died as a result of torture which caused several lacerations and bruises until the victim finally died. The perpetrators of this case are known to be the victim's step-grandmother, the victim's step-mother and none other than the victim's biological father.